Green Economy of Plastic Value Chain Opportunity from Circular Economy Perspective - Purwanto, Setiyo; Wuryandari, Nur Endah Retno; Hasana, Rizka Amalia Nur (Universitas Pendidikan Indonesia, 2024)
This study aims to examine the recycled plastic industry's competitiveness and supply chain strategy in Indonesia mediated by import regulations to improve the company's financial performance. Building the concept of circular economy in the green supply chain management framework. Optimizing the management and development of the recycled plastic industry also provides a multiplayer effect on product competitiveness, creates a green economy and green environment, and contributes to reducing virgin plastic import consumption. This research is based on quantitative methodology with population data from business people and employees within the scope of recycling plastic industry activities in the DKI Jakarta area. The Slovin formula produces a purposeful random sampling method for the respondent sample data collecting approach. This research was conducted by collecting questionnaires from respondents. The data was processed using SEM analysis tools on the SmartPLS 3.3 statistical application program. The results showed that innovation, investment, and import and export regulations from the government were able to increase the competitiveness of domestic plastic recycling products from a circular economy perspective. In addition, supported by good green supply chain management, it can improve the company's financial performance.